2022
DOI: 10.1002/cssc.202200392
|View full text |Cite
|
Sign up to set email alerts
|

Cu−NPs@C Nanosheets Derived from a PVP‐assisted 2D Cu‐MOF with Renewable Ligand for High‐Efficient Selective Hydrogenation of 5‐Hydroxymethylfurfural

Abstract: 5-Hydroxymethylfurfural (HMF) containing C=O, CÀ O, and furan ring functional groups is an important platform chemical derived from C 6 sugars. The selective hydrogenation of C=O in HMF produces 2,5-dihydroxymethylfuran (DHMF), which is a potential sustainable substitute for petroleum-based building blocks. Here, 2,5-furandicarboxylic acid (H 2 FDC), a promising sustainable alternative to terephthalic acid, was employed as a renewable ligand to synthesize a novel Cu metal-organic framework (Cu-FDC). With a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The ligand is essential to the preparation of MOFs, and a large number of ligands are derived from non-renewable fossil resources. Bao et al (Bao et al 2022 ) employed renewable HMF-derived 2,5-furandicarboxylic acid as ligand to synthesize a novel Cu-based MOFs, and Cu NPs supported on carbon nanosheets were fabricated by post-treatment of the MOFs. The as-prepared Cu catalysts exhibited good catalytic activity and stability for the hydrogenation of HMF to FDM, providing a 99.4% yield.…”
Section: Synthesis Of Fdm From Hmfmentioning
confidence: 99%
“…The ligand is essential to the preparation of MOFs, and a large number of ligands are derived from non-renewable fossil resources. Bao et al (Bao et al 2022 ) employed renewable HMF-derived 2,5-furandicarboxylic acid as ligand to synthesize a novel Cu-based MOFs, and Cu NPs supported on carbon nanosheets were fabricated by post-treatment of the MOFs. The as-prepared Cu catalysts exhibited good catalytic activity and stability for the hydrogenation of HMF to FDM, providing a 99.4% yield.…”
Section: Synthesis Of Fdm From Hmfmentioning
confidence: 99%
“…[140] Bao et al also reported that a 2D oxygen-rich carbon nanosheets embedded with Cu nanoparticles (Cu-NPs@C) prepared via pyrolysis of nano-lamellae Cu-FDC exhibited excellent performance and stability for the selective hydrogenation of HMF to DHMF (see Figure 15B). [141] Wu and co-workers disclosed that small Pd nanoparticles could be stabilized in MOF-303 by the adjacent pair of N atoms of organic linkers (Pd@MOF-303), and the yield of DHMTHF was 95.8 % under 1 MPa H 2 due to the exposure of plenty of stable defective sites on Pd nanoparticles. [142] Karve et al had developed a palladium-functionalized MOF/polymer composite, Reproduced with permission from ref.…”
Section: (B)mentioning
confidence: 99%
“…Nevertheless, compared to the classical ligand, H 2 FDC-related MOFs are still relatively few, with only about 100 associated reports. Also, the applications of such MOFs are mainly focused on luminescence, gas adsorption, and catalysis, and only one MOF related to proton conductivity has been involved …”
Section: Introductionmentioning
confidence: 99%